Dissociative, depressive, and PTSD symptom severity as correlates of nonsuicidal self-injury and suicidality in dissociative disorder patients. Issue 1 (1st January 2016) - Webermann, Aliya R.; Myrick, Amie C.; Taylor, Christina L.; Chasson, Gregory S.; Brand, Bethany L.
ABSTRACT: The present study investigates whether symptom severity can distinguish patients diagnosed with dissociative identity disorder and dissociative disorder not otherwise specified with a recent history of nonsuicidal self-injury (NSSI) and suicide attempts from those patients without recent self-harm. A total of 241 clinicians reported on recent history of patient NSSI and suicide attempts. Of these clinicians' patients, 221 completed dissociative, depressive, and posttraumatic stress disorder symptomatology measures. Baseline cross-sectional data from a naturalistic and prospective study of dissociative disorder patients receiving community treatment were utilized. Analyses evaluated dissociative, depressive, and posttraumatic stress disorder symptom severity as methods of classifying patients into NSSI and suicide attempt groupings. Results indicated that dissociation severity accurately classified patients into NSSI and suicidality groups, whereas depression severity accurately classified patients into NSSI groups. These findings point to dissociation and depression severity as important correlates of NSSI and suicidality in patients with dissociative disorders and have implications for self-harm prevention and treatment.